First Report of Necrotic Spot Disease Caused by Cactus virus X on Dragon Fruit (Hylocereus spp.) in Peninsular Malaysia - Masanto Masanto; Kamaruzaman Sijam; Yahya Awang; Mohd Ghazali Mohd Satar (Universitas Gadjah Mada, 2018)
This study was conducted to detect the status of virus causing necrotic spot disease on dragon fruit and to recognize its geographical distribution in Peninsular Malaysia. Fifty posts of crops were randomly sampled from dragon fruit orchards. The symptoms were characterized and the pathogen was observed under transmission electron microscopy (TEM). Disease incidence and severity were plotted, while the disease occurrence was statistically analyzed under Duncan’s Multiple Range Test (DMRT) of General Linear Modeling (GLM) procedure and Pearson correlation test. The disease was initiated by necrotic small mottle or spot on young shoot which then turned to orange. Those symptoms were also found on mature stems and fruits. They could quickly expand on unexposed symptomatic parts in orchards. The maximum incidence and severity of disease were recorded in Durian Tunggal (Malacca), i.e. 98 and 52%, respectively. TEM technique viewed the spindle-shaped inclusion bodies of virus within symptomatic stems at 4000 and 20,000X magnification which were suspected as Cactus virus X (CVX), a potexvirus with filamentous and rod shape and 515−520 nm in size. Statistically, disease occurrence in Malacca was significantly higher than those in other states, while the minimum was found in Terengganu. The strong regression of disease incidence and severity was shown by R value= 0.9484. There were no significant correlations of disease occurrence, either with weather or cultural factors. Further study on the transmission of virus within the crops in the field is important to be carried out in order to monitor the spread of disease and to develop the integrated disease management strategies on dragon fruit in Peninsular Malaysia. IntisariKajian ini dilakukan untuk mendeteksi status virus yang menyebabkan penyakit bercak nekrotik pada buah naga dan untuk mengetahui distribusi geografisnya di Semenanjung Malaysia. Lima puluh tiang tanaman disampel secara acak dari kebun buah naga. Gejala-gejala dikarakterisasi dan patogen diamati di bawah transmission electron microscopy (TEM). Insidensi dan keparahan penyakit diplot, sedangkan kejadian penyakit secara statistik dianalisis menggunakan Duncan Multiple Range Test (DMRT), General Linear Modeling (GLM) dan uji Pearson correlation. Penyakit dimulai dengan bercak nekrotik kecil pada tunas muda dan kemudian berubah menjadi jingga. Gejala-gejala tersebut juga dijumpai pada batang dewasa dan buah. Penyakit dapat berkembang dengan cepat pada bagian bergejala yang tidak terlihat di kebun. Insidensi dan keparahan penyakit yang paling banyak ditemukan di Durian Tunggal (Melaka), yaitu masing-masing 98 dan 52%. Teknik TEM menunjukkan badan inklusi berbentuk benang dari virus pada batang yang bergejala pada perbesaran 4000 dan 20.000X yang diduga sebagai Cactus virus X (CVX), suatu potexvirus yang berbentuk benang dan batang serta berukuran panjang 515–520 nm. Secara statistik, kejadian penyakit di Melaka secara nyata lebih tinggi daripada di negara bagian lainnya, sedangkan kejadian penyakit yang paling sedikit dijumpai di Terengganu. Regresi insidensi dan keparahan penyakit yang kuat ditunjukkan oleh nilai R= 0,9484. Tidak ada korelasi nyata kejadian penyakit, baik dengan faktor cuaca maupun budidaya. Kajian lebih lanjut terkait penularan virus dalam tanaman di lapangan penting untuk dilakukan dalam rangka memantau penyebaran penyakit dan untuk mengembangkan strategi pengendalian penyakit yang terpadu pada buah naga di Semenanjung Malaysia.